Fulfillment of administrative and professional obligations of hospitals and mission motivation of physicians - Trybou, Jeroen (BMC Health Serv Res, 2017)
BACKGROUND: To be successful, hospitals must increasingly collaborate with their medical staff. One strategic tool that plays an important role is the mission statement of hospitals. The goal of this research was to study the relationship between the fulfillment of administrative and professional obligations of hospitals on physicians’ motivation to contribute to the mission of the hospital. Furthermore the mediating role of the physicians’ emotional attachment to the hospital and moderation effect of the exchange with the head physicians were considered. METHODS: Self-employed physicians of six hospitals participated in a survey. Descriptive analyses and linear regression were used to analyse the data. RESULTS: The results indicate that affective commitment mediated the relationship between psychological contract fulfillment and mission statement motivation. In addition, the quality of exchange with the Chief Medical Officer moderated the relationship between the fulfillment of administrative obligations and affective commitment positively. CONCLUSION: This study extends our understanding of social exchange processes and mission statement motivation of physicians. We showed that when physicians perceive a high level of fulfillment of their psychological contract they are more committed and more motivated to contribute to the mission statement. A high quality relationship between physician and Chief Medical Officer can enhance this reciprocity dynamic. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-017-1990-0) contains supplementary material, which is available to authorized users.